Empowerment of Public Health Students as Agents of Behavior Change in The Prevention and Control of Diabetes Mellitus in Tafraka Village Pulau Hiri District, Ternate City, Indonesia - Nursia Aja; Ismawanti Sawedi; Hairudin La Patilaiya; Norma B. Toduho (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Diabetes Mellitus (DM) is a non-communicable disease (NCD) that is a major health problem worldwide, including in Indonesia. Data from the Indonesian Ministry of Health shows that the prevalence of diabetes continues to increase annually, not only among the elderly but also among those of productive age and adolescents. The main objective of this empowerment program is to enhance the role and capacity of public health students as agents of behavior change through a community-based empowerment approach, specifically in Tafraka Village, Pulau Hiri District, Ternate City. With this approach, students are expected to contribute significantly to increasing public awareness, knowledge, and healthy lifestyles related to the prevention and control of diabetes mellitus. The empowerment program begins with a preparation phase, strengthening the students' capacity as agents of behavior change. At this stage, coordination is carried out with various stakeholders, including educational institutions, community health centers, and community leaders, to determine the location and target groups for the activities. Students of the Public Health Study Program, Faculty of Health Sciences. The results of the activity showed that the empowerment approach involving students of the Public Health Study Program of the Faculty of Health Sciences in the Field Learning Experience (PBL) 2 activity in Tafraka Village, Pulau Hiri District, was effective in increasing public knowledge and awareness of efforts to prevent and control Diabetes Mellitus. The conclusion of the empowerment activity of Public Health students as agents of behavior change in Tafraka Village, Pulau Hiri District, Ternate City showed that the active involvement of students in community education and mentoring activities was able to increase public knowledge, attitudes, and awareness of the importance of preventing and controlling Diabetes Mellitus.